2013
DOI: 10.1039/c3ta01099f
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle doped hollow SnO2 supersymmetric nanostructures for improved photocatalysis

Abstract: Hollow SnO 2 supersymmetric nanostructures with high surface area were synthesized by a solution reaction with N,N-dimethylformamide (DMF) as a solvent in the presence of PVP and PEG as capping agents. It was demonstrated that the initially formed ultrafine SnO 2 nanoclusters assembled to form hollow hexapods, and then the further in situ self-assembly induced the formation of higher-ordered hollow structures. After depositing gold nanoparticles (NPs) onto them, the structures presented an enhanced photocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…The XRD and FTIR images are used to demonstrate the growth mechanism of the rodlike precursor. The crystalline structure of the precursor and the diffraction peaks similar to those of Zn–EG,20 Sn–EG,21 and Ti–EG,22 especially the strong peak located in the low‐angle region (≈10°), are shown in Figure 1 c. In the FTIR spectrum of the rodlike precursor (Figure 1 d), absorption peaks in the range of 2850–2950 cm −1 correspond to υ as and υ s (CH) bands, absorption peaks at approximately 1700 cm −1 correspond to CO bands, and absorption peaks in the range of 1060–1120 cm −1 correspond to ρ(CH 2 ), υ(CO), and υ(CC) bands 23.…”
Section: Resultsmentioning
confidence: 86%
“…The XRD and FTIR images are used to demonstrate the growth mechanism of the rodlike precursor. The crystalline structure of the precursor and the diffraction peaks similar to those of Zn–EG,20 Sn–EG,21 and Ti–EG,22 especially the strong peak located in the low‐angle region (≈10°), are shown in Figure 1 c. In the FTIR spectrum of the rodlike precursor (Figure 1 d), absorption peaks in the range of 2850–2950 cm −1 correspond to υ as and υ s (CH) bands, absorption peaks at approximately 1700 cm −1 correspond to CO bands, and absorption peaks in the range of 1060–1120 cm −1 correspond to ρ(CH 2 ), υ(CO), and υ(CC) bands 23.…”
Section: Resultsmentioning
confidence: 86%
“…Tin (IV) oxide (SnO 2 , stannic oxide) is an n ‐type semiconductor with a wide band gap of about 3.6 eV that has been extensively studied due to its potential application in sensors, batteries/electrodes, solar cells, and catalysts . Most studies have focused on modifying the nanostructures for SnO 2 and studying their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on modifying the nanostructures for SnO 2 and studying their properties. To accomplish this, various experimental conditions employing wet chemical (e.g., hydrothermal and solvothermal) and dry physical (e.g., chemical vapor deposition) methods have been employed to develop various morphologies such as wires, nanorods, hierarchical nanosheets, and cubes . Xi and Ye synthesized ultra‐small (2 nm) SnO 2 nanorods with a high specific area of 191.5 m 2 /g, while Sun et al .…”
Section: Introductionmentioning
confidence: 99%
“…These include Cu-doped SnO 2 film for H 2 S sensing 33 , multi-layer SnO 2 nanoplates 34 and flower-like SnO 2 for ethanol sensing 35 , aligned epitaxial SnO 2 nanowires for ppb-level NO 2 sensing 36 , p-Te/n-SnO 2 hierarchical heterostructures 37 and SnO 2 hollow spheres for ppm-level CO sensing 38 , hollow SnO 2 nanofibers 39 and graphene/SnO 2 hybrids 40 for H 2 sensing, clustered SnO 2 NPs for toluene detection 41 , and SnO 2 NP-coated ZnO nanotubes for electrochemical dopamine sensing 42 , For solar cell applications 48 49 50 51 , Dong et al reported that quintuple-shelled SnO 2 hollow microspheres showed superior light scattering suitable for dye-sensitized solar cells 50 . The (thermal and photo) catalytic activity of SnO 2 has also been studied actively 52 53 54 55 56 57 . Several examples include the inactivation of bacteria using fluorinated SnO 2 hollow nanospheres 52 , rhodamine B treatment using flower-like hollow SnO/Sn 3 O 4 microspheres 53 , Rhodamine 6G photodegradation using hollow supersymmetric SnO 2 microspheres 54 .…”
mentioning
confidence: 99%
“…The (thermal and photo) catalytic activity of SnO 2 has also been studied actively 52 53 54 55 56 57 . Several examples include the inactivation of bacteria using fluorinated SnO 2 hollow nanospheres 52 , rhodamine B treatment using flower-like hollow SnO/Sn 3 O 4 microspheres 53 , Rhodamine 6G photodegradation using hollow supersymmetric SnO 2 microspheres 54 . SnO 2 nanorods with exposed (110) facets were reported to have high CO oxidation activity following a Mars–van Krevelen mechanism, even though the nanorods have a low surface area and a less active surface oxygen species 55 56 .…”
mentioning
confidence: 99%